Prognozowanie w zarządzaniu energią - Gładysz, Barbara; Kołwzan, Wiktor; Mercik, Jacek (Forecasting in Energy Supply Management, 2006)
The analysis of capacity of electricity system was done for years 1998-2001 (30.000 observations). The significant factors were established. Among them there are: consumption of Energy in previous periods, seasonality, cyclicality, atmospheric temperature, energy weekly demand structure. Those factors were used as exaplanation variables in econometric models. The delay variables were also used. The models were constructed for homogenous classes of data. Afterwards, models were used for forecasting. Prognostics errors for different classes were compared. Magnitude of errors depends on time horizon and homogeneity of data.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 197-206